2017
DOI: 10.1155/2017/9623620
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Polymer Binder on the Transparent Conducting Electrodes on Stretchable Film Fabricated by Screen Printing of Silver Paste

Abstract: Smart wearable devices and sensors have been fabricated by screen printing of metal paste as functional circuits since the metal interconnects exhibited much less electrical resistance than other conducting materials such as carbon nanotube or conducting polymers (PEDOT:PSS). In this study, we chose silver particle as conductive material in the form of silver paste and used screen printing to fabricate a stretchable touch screen panel utilizing metal mesh method for the transparent electrode patterning. The rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Metallic pastes deliver a desirable processing format for screen-printed conductors for electronic applications. Such pastes are typically composed of conductive fillers, organic vehicles of both binders and solvents, inorganic binders, and additives such as dispersants to tune the overall paste functionality. , Accordingly, in order for these core–shell nanoparticles to be usable in realistic applications, further work is needed to formulate them into a suitable conductive paste. Thus, for the first time, we perform a systematic study to understand how organic vehicles in pastes synthesized following the procedure detailed in the Experimental Section mentioned below, including both organic binders and organic hardeners, affect the morphology and electrical and optical properties of printed conductors made out of copper–silver core–shell nanoparticles, aiming to deliver a cost-effective paste for potential printed-conductor applications.…”
Section: Resultsmentioning
confidence: 99%
“…Metallic pastes deliver a desirable processing format for screen-printed conductors for electronic applications. Such pastes are typically composed of conductive fillers, organic vehicles of both binders and solvents, inorganic binders, and additives such as dispersants to tune the overall paste functionality. , Accordingly, in order for these core–shell nanoparticles to be usable in realistic applications, further work is needed to formulate them into a suitable conductive paste. Thus, for the first time, we perform a systematic study to understand how organic vehicles in pastes synthesized following the procedure detailed in the Experimental Section mentioned below, including both organic binders and organic hardeners, affect the morphology and electrical and optical properties of printed conductors made out of copper–silver core–shell nanoparticles, aiming to deliver a cost-effective paste for potential printed-conductor applications.…”
Section: Resultsmentioning
confidence: 99%
“…High-performance FTEs can be prepared by combining CPs with other conductive materials, such as metals or carbon-based materials (graphene and CNTs). Lim et al found that silver electrodes prepared with polymer-added silver paste have high conductivity [115]. Rahman et al obtained free-forming gel polymer electrolyte (GPE) samples with variable shapes and sizes by 3D printing (Figure 7), and the addition of N,N-dimethylacrylamide (DMAAm) into the polyvinylidene fluoride (PVDF) network significantly improved the tensile elongation (up to 200%) and mechanical properties of GPE [116].…”
Section: Conductive Polymersmentioning
confidence: 99%
“…The electrical conductance of the paste is known to be highly dependent on the percolation pathway of the conductive fillers (i.e., metallic particles or flakes) in an interconnected network structure . However, the binder material, which is as important as the conductive fillers, determines the physical outcome of the conducting paste including its adhesion to the substrate, mechanical hardness, and flexibility, as well as the creation of a conductive path by forming a filler-to-filler connection. , First-generation conducting paste contained glass frits as a binder, which showed good adhesion to silicon or a glass substrate . However, its usage requires high-temperature heating above 400 °C to melt the glass frits, which limits its application to various electronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, their physical and chemical properties can easily be adjusted by changing the molecular design of the resin. To date, a variety of polymers including epoxy resins, polyacrylates, polyurethanes (PU), polyimides (PI), and phenolic resins has been utilized as a binder for conducting pastes. ,,, Even though further improvement is needed from the viewpoint of resistivity and the processing conditions, conducting pastes based on some of these polymer adhesives have been commercialized because of the sufficiently low resistance and good adhesion properties they exhibit. However, the use of these polymer resins, in fact, is gradually being restricted owing to either the raw materials or the production processes being hazardous to humans.…”
Section: Introductionmentioning
confidence: 99%